STRATEGI PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN HUTAN DAN LAHAN OLEH BADAN PENANGGULANGAN BENCANA DAERAH DI KECAMATAN KEMUNING KABUPATEN INDRAGIRI HILIR TAHUN 2023 - Lusiana, Fani; Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Kemuning District is one of the regions in Indragiri Hilir Regency that has experienced a significant increase in forest and land fire (Karhutla) cases. Therefore, a strategy is required by the Regional Disaster Management Agency (BPBD) of Indragiri Hilir Regency to address this issue. Karhutla in Kemuning District is usually caused by land clearing activities by local residents during the dry season. This research aims to examine the prevention and mitigation strategies for Karhutla by BPBD in Indragiri Hilir Regency, particularly in Kemuning District. The research location is in Indragiri Hilir Regency, specifically in Kemuning District, due to the significant increase in Karhutla cases in this area. This study employs the strategy theory proposed by Fred R. David, which includes formulating, implementing, and evaluating decisions to achieve goals, and it adopts a descriptive qualitative approach. Data collection techniques include interviews and documentation, while the data analysis technique follows the data collection methods of Miles and Huberman. The results show that the BPBD strategy in Indragiri Hilir Regency has not been fully successful in managing Karhutla, as there are still residents who are unaware of the disaster risks and relevant regulations related to Karhutla. Several obstacles were identified, including limited facilities and infrastructure, a lack of specialized human resources, and suboptimal budget allocation. Additionally, a large portion of Indragiri Hilir Regency consists of peatland areas, making it highly susceptible to Karhutla, especially during the dry season. Efforts by BPBD to prevent and manage Karhutla in Indragiri Hilir Regency include implementing various strategies such as disaster management programs/activities, starting from pre-disaster, emergency response, to post-disaster stages. However, there are still some programs/activities whose implementation is considered less than optimal. Keywords: Strategy, BPBD, Management, Disaster, Forest and Land Fires.